ANALISIS PERILAKU SOSIAL ANAK USIA 5-6 TAHUN DI TK LABORATORIUM FKIP UNIVERSITAS RIAU - Sri Aflianna Hasibuan; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the social behavior of cooperation, competition, support, sympathy, empathy, sharing, familiarity, imitation, and knowing the development of social behavior of children aged 5-6 years in the fkip laboratory of the university of riau. As for the population in this study, the B1 and B2 classes were 41 children and the sample in this study ampunted to 41 children. This research was conducted on independent variables, without making comparisons or connecting with other variables. the approach used in this study is a quantitative descriptive approach (describing research results based on numbers) based on the results of the study it can be concluded that the development of successful social behavior in children aged 5-6 years in the fkip laboratory of riau university is included in the BSH category because it has an average of 73,47%Key Words: Analysis, Social behavior